Communication Process for the Strengthening of the Care of the Minor in a Pediatric Unit (2018)
Introduction: The reflection about the elements of communication that health professionals use strengthens the empathic relationship and therefore the actions that seek self-care in patients. Nursing schools must teach how to acquire competences from what should be (moral) to fully consider the emotions and needs of hospitalized children so that they can attend to the call of care. Nursing should tend to social and communication skills to offer a humanized care when children appeal to crying, to silence, to play, to attract attention. Objective: Propose a framework of moral management of communication from the design of a functional communication structure model for the pediatric patient to come to the call of their care in a positive way. Methodology: Nature of qualitative study of descriptive type and symbolic interactionism (perceptual regression). The population was 44 nurses. The data was obtained by interviews analyzed by the STATGRAPHICS XVII Centurión Plus® and Atlas Ti 8.0 ® programs. Conclusion: The practices of nurses respond to the dynamics so that the child comes to the care when they are aware of the purpose of communication in strengthening the moral development of the child. A model of functional communication structure for pediatric patient care adjusted to the axioms of Paul Watzlawick is proposed.